Tools, harmonization and standardization procedures of the impact and outcome evaluation indices obtained during a kindergarten‐based, family‐involved intervention to prevent obesity in early childhood: the ToyBox‐study. (August 2014) - Mouratidou, T.; Miguel, M. L.; Androutsos, O.; Manios, Y.; De Bourdeaudhuij, I.; Cardon, G.; Kulaga, Z.; Socha, P.; Galcheva, S.; Iotova, V.; Payr, A.; Koletzko, B.; et al.
Summary: The ToyBox‐intervention is a kindergarten‐based, family‐involved intervention targeting multiple lifestyle behaviours in preschool children, their teachers and their families. This intervention was conducted in six European countries, namely Belgium, Bulgaria, Germany, Greece, Poland and Spain. The aim of this paper is to provide a descriptive overview of the harmonization and standardization procedures of the baseline and follow‐up evaluation of the study (and substudies). Steps related to the study's operational, standardization and harmonization procedures as well as the impact and outcome evaluation assessment tools used are presented. Experiences from the project highlight the importance of safeguarding the measurement process to minimize data heterogeneity derived from potential measurement error and country‐by‐country differences. In addition, it was made clear that continuing quality control and support is an important component of such studies. For this reason, well‐supported communication channels, such as regular email updates and teleconferences, and regular internal and external meetings to ensure smooth and accurate implementation were in place during the study. The ToyBox‐intervention and its harmonized and standardized procedures can serve as a successful case study for future studies evaluating the efficacy of similar interventions.